2002
DOI: 10.1016/s0002-9440(10)64225-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hair Follicle Morphogenesis and Cycling with Abnormal Epidermal Differentiation in nackt Mice, a Cathepsin L-Deficient Mutation

Abstract: We previously described an autosomal-recessive mutation named nackt (nkt) exhibiting partial alopecia associated with CD4(+) T-cell deficiency. Also, we recently reported that nkt (now Ctsl(nkt)) comprises a deletion in the cathepsin L (Ctsl) gene. Another recent study reported that Ctsl knockout mice have CD4(+) T-cell deficiency and periodic shedding of hair, which recapitulate the nkt mutation and the old furless (fs) mutation. The current study focuses on the dermatological aspects of the nkt mutation. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…As it has been shown for asebia mice, Ctsl Ϫ/Ϫ mice have a prolonged anagen phase/delayed catagen entry (48,50). Similarly, preliminary data suggest a prolonged growing phase (morphogenesis and anagen) also in Fa2h Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 61%
“…As it has been shown for asebia mice, Ctsl Ϫ/Ϫ mice have a prolonged anagen phase/delayed catagen entry (48,50). Similarly, preliminary data suggest a prolonged growing phase (morphogenesis and anagen) also in Fa2h Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 61%
“…However, there is growing evidence for specific intra-and extracellular functions for CTSL in MHC-II antigen presentation (Honey and Rudensky, 2003), prohormone processing (Friedrichs et al, 2003;Yasothornsrikul et al, 2003) and other processes involving limited proteolysis (Turk et al, 2001). Major insights into the function of cathepsin L in the skin result from analysis of mice with targeted inactivation of the CTSL gene (ctsl -/-mice) and from the spontaneous mouse mutations nackt (ctsl nkt /ctsl nkt ) and furless (fs -/fs -) for which the cathepsin L gene has been identified as the target (Benavides et al, 2002;Roth et al, 2000). Cathepsin L-deficient (ctsl -/-) mice develop periodic hair loss, gingival acanthosis and epidermal hyperplasia with hyperkeratosis (Nishimura et al, 2002;Tobin et al, 2002).…”
mentioning
confidence: 99%
“…Impaired differentiation of hair follicle epithelial cells and hyperproliferation of basal epidermal keratinocytes are the primary characteristics of the ctsl -/-phenotype. Organ cultures of neonatal ctsl -/-mouse skin and crossing of Rag2 -/-mice with ctsl nkt /ctsl nkt mice (Benavides et al, 2002) revealed that the skin phenotype is independent of systemic, i.e. immunological, effects.…”
mentioning
confidence: 99%
“…They are involved in proteolytic processing of proteins in the endocytic pathway, including peptide growth factors that are internalized in a complex with their plasma membrane receptors (Authier et al, 1999). Recent studies with CathLdeficient mice have implicated this enzyme in several developmental processes, including epidermal homeostasis and hair follicle development (Reinheckel et al, 2001;Benavides et al, 2002).…”
Section: Introductionmentioning
confidence: 99%